Anticonvulsant activity and mechanism of actions of fractions of Ipomoea asarifolia (Desr) (Convolvulaceae) ethanol leaf extract - Samaila S. Chiroma; Abdullahi B. Nazifi; Ya’u Jamilu; Aliyu Musa; Lawal A. Bichi; Samaila M. Chiroma (Bulletin of the National Research Centre, 2022)
Abstract Background Preparation of Ipomoea asarifolia (Desr) (Convolvulaceae) is widely used in traditional African medicine for the treatments of different kinds of ailments such as syphilis, malaria, convulsions and rheumatism. Aim The anticonvulsant properties of fractions of leaf of Ipomoea asarifolia (Desr); n-butanol (BF), chloroform, n-hexane and residual aqueous fractions (RAF) were evaluated on animals. Results The RAF at dose of 75 mg/kg (P < 0.01) with 33% quantal protection and 83% protection against mortality is the most active fraction when compared with BF at 300 mg/kg (P < 0.01) with no quantal protection and 83% protection against mortality; the anti-seizure activity could be because of the presence of saponins (23.3%) and flavonoids (43.92%). The RAF may also owes its anticonvulsant activity via GABAergic pathway as flumazenil at 2 mg/kg significantly (P < 0.05) blocked the activity of RAF, via glutamatergic pathway with RAF (P < 0.05) significantly reversing the proconvulsive activity of ketamine at 200 mg/kg as compared to ketamine alone. Opioidergic pathway may also be implicated as naloxone 1 mg/kg significantly (P < 0.05) reduced the anticonvulsant effect of RAF. Conclusions BF and RAF of leaf of Ipomoea asarifolia have shown anticonvulsants activities in PTZ-induced seizures. RAF was observed to be the most active fraction of Ipomoea asarifolia extract which probably exerts its action through GABAergic, glutamatergic and opioidergic pathways.